Influence of ink and smoke ATM security systems on dactyloscopy and subsequent DNA analysis after detonation. (September 2021) - De Smet, Margot; Ramaekers, Kato; Verhoeven, Elke; Vermeulen, Steve; Bekaert, Bram
Abstract: Automated Teller Machine bombings are an increasing societal problem that are often committed using Improvised Explosive Devices. The evolution in IEDs and the negative consequences for society require new security measures to prevent these crimes. Ink staining and security smoke devices are added to cash cassettes, in order to protect ATMs and prevent ATM bombings. Traces found at crime scenes, such as fingerprints and DNA, can contribute to the identification of perpetrators. However, the effect of ink staining and security smoke devices on dactyloscopy and DNA profiling is still unknown. In the current study, we demonstrate that procedures using Citrus Cleaner or sulfosalicylic acid were successful in removing ink and security smoke deposited on plastic plates but did result in the massive loss of fingerprint information as only a low number (4%) of good quality fingerprints were recovered after smoke contamination. Secondly, security ink Sun Blue ES2, but not SICPA Green and Sun Blue ES1, had a significant impact on DNA profiling success. DNA concentrations obtained from blood spiked swabs decreased with increasing ink concentration resulting in a complete loss of genotype information with the addition of ≥ 10 μ l Sun Blue ES2. No noticeable PCR inhibition or DNA degradation was detected during quantification, but a decreased efficiency of DNA extraction could not be excluded. Security smoke, on the other hand, does not seem to have a significant influence on DNA analysis. Precautions must therefore be taken in order to avoid contaminating DNA swabs with ink during sampling. Thirdly, only a single negative impression of a glove in ink and a single glove print were able to be visualized with white fingerprint powder on detonated cash cassettes. In conclusion, the detection of glove prints and fingerprints is limited and security ink, contrary to smoke, after detonation can have a negative influence on downstream DNA analysis procedures. Highlights: Determine influence of ATM security systems on dactyloscopy and DNA profiling. Ink and smoke ATM security systems negatively affect dactyloscopy success rates. ATM security ink Sun Blue ES2 has a significant negative effect on DNA yield after DNA-extraction and STR genotyping. Glove print analysis on cash cassettes is limited.